Certain Integral and Differential Formulas Involving the Product of Srivastava’s Polynomials and Extended Wright Function - Saima Naheed; Shahid Mubeen; Gauhar Rahman; Zareen A. Khan; Kottakkaran Sooppy Nisar (Fractal and Fractional, 2022)
Many authors have established various integral and differential formulas involving different special functions in recent years. In continuation, we explore some image formulas associated with the product of Srivastava’s polynomials and extended Wright function by using Marichev–Saigo–Maeda fractional integral and differential operators, Lavoie–Trottier and Oberhettinger integral operators. The obtained outcomes are in the form of the Fox–Wright function. It is worth mentioning that some interesting special cases are also discussed.